Scalable Production of Edge-Functionalized Graphene Nanoplatelets via Mechanochemical Ball-Milling - Jeon, In-Yup; Bae, Seo-Yoon; Seo, Jeong-Min; Baek, Jong-Beom (Advanced functional materials, 2015)
Although there are a variety of methods for producing graphene, commercialization remains challenging because each method has its own pros and cons. For the wide use of graphene as a next generation material in diverse applications, the process by which graphene is manufactured must be robust enough to overcome barriers to commercialization, as has been experienced in commercializing carbon nanotube products. Here, a recent discovery of a new manufacturing process for efficient delamination of graphite into graphene nanoplatelets (GnPs) via mechanochemical ball‐milling is summarized. In this process, transferring sufficient kinetic energy to graphitic frameworks will crack graphitic C–C bonds, generate active carbon species (mostly carbon free radicals), introduce edge‐functional groups, and delaminate graphitic layers into edge‐functionalized GnPs (EFGnPs). While this process is a method for mass production, it does not involve hazardous chemicals (e.g., corrosive acids and toxic reducing agents) such as those used for producing graphene oxide (GO) and reduced graphene oxide (rGO). Owing to its edge‐selective functionalization, the EFGnPs have minimal basal area defects with selectivity of a variety of edge groups by forming edge C–X bonds (X = nonmetals or metalloids) that are tunable. A method for producing edge‐selectively functionalized graphene nanoplatelets (EFGnPs) is developed by simple mechanochemical ball‐milling graphite in the presence of the desired reactant(s). Due to their advantages such as manufacturing simplicity, edge‐selectivity, eco‐friendliness, low‐cost and high‐quality over other commonly used methods, EFGnPs have potential in a broad range of applications.